Road traffic safety on the roundabouts - Степанчук, О. В.; Васюкович, Д. Б. (Proceedings of National Aviation University, 2013)
The growth of automobilization and the noncompliance of the city central parts with the modern vehicles requirements create the preconditions for the increase of the road traffic accidents. the intersections, of the main streets of the district value are the most accidental. It is noted that to develop a set of measures to improve road safety at the intersections it is necessary to know the degree of their security. it is found that that the intersections of highways significantly reduce the capacity, creating significant delay of traffic flows, as a result of which they become places of high concentration of automobile emissions, noise and other adverse effects on the environment